Coberturas poliméricas incorporadas de extrato da casca do cajueiro aplicadas em queijo coalho - Rabelo, José Lucas Girão (2023)
The objective of the research was to develop edible coatings of blends of chitosan and cassava starch, added with cashew bark extract (Anacardium occidentales L.), and the characterization of their effects on the microbiological quality of Coalho cheese. The first part of the work involved the application of an online questionnaire, which aimed to obtain information about the profile of consumers and their knowledge about the use of edible coatings in Coalho cheese, and their influence on the purchasing and consumption habits of the cheese. The experiment was carried out producing the hydroethanolic extract (70%) from the cashew stem bark (ECC) (bark/ethyl alcohol ratio 1:9 m/v). (CFT), antioxidant activity (AA) (ABTS+ and FRAP methods), antimicrobial activity (Staphylococcus aureus), minimum inhibitory concentration (MIC) and minimum bactericidal concentration (MBC) and acute toxicity test using adult zebrafish. Subsequently, formulations of coatings and polymeric blends of chitosan (2%) and cassava starch (3%) added with cashew bark extract (2%, v/v) were produced and evaluated for CFT, AAT, color, properties rheology, contact angle and scanning electron microscopy (SEM). Subsequently, pieces of Coalho cheese were covered with coatings and polymeric blends with and without extract to evaluate their antimicrobial effect (Coagulase positive Staphylococci) on the product. The ECC showed values of CFT content of 42.17 mg EAG/ml, AA of 551.158 μM of Trolox/ml and 1006.44 μM of FeSO4/ml. Inhibition halos against Staphylococcus aureus ranging from 13.0mm, 15.3mm, 16.7mm, 20.0mm for concentrations of 6.25%, 12.5%, 25% and 100%, MIC and MBC of 1%, showed no toxicity at concentrations below 100%. The coatings and blends added with ECC (2%) showed different levels of CFT (F100, 0.660 mg of EAG/ml; F50Q50, 0.850 mg of EAG/ml and F60Q40, 0.835 mg of EAG/ml), as well as AA (F100 , 3.57 μM Trolox/ml; F50Q50, 4.52 μM Trolox/ml; F60Q40, 4.95 μM Trolox/ml; F100, 26.42 μM FeSO4/ml; F50Q50, 15.86 μM Trolox/ml FeSO4/ml; F60Q40, 18.05 μM FeSO4/ml).The added coatings of ECC reduced the growth of coagulase positive Staphylococci in Coalho cheese samples stored for 10 days. Therefore, the addition of ECC provided antimicrobial and antioxidant characteristics to the starch and chitosan coatings, in addition to increasing the shelf life of Coalho cheese by inhibiting the growth of coagulase-positive Staphylococci, adding value to the product.